Optimized Synthesis of FeNi/TiO2 Green Nanocatalyst for High-Quality Liquid Fuel Production via Mild Pyrolysis - Riny Yolandha Parapat; Muhamad Firmansyah Rizkiawan Putra; Zamaludin Zamaludin; Didin Agustian Permadi; Imam Aschuri; Yuono Yuono; Alfian Noviyanto; Michael Schwarze; Reinhard Schomäcker (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2023)
In sustainable energy improvement, the strategic design of economical nanocatalysts has emerged as a pivotal pathway, notably within intricate processes such as asphalt pyrolysis. This study presents a new endeavor, conceptualizing a non-precious metal nanocatalyst FeNi deposited on TiO2, synthesized through an environmentally conscious green synthesis methodology employing mangosteen peel extract as a sustainable reductant. Asphalt, the most complex compound, is used as the pyrolyzed material to measure the activity of nanocatalysts in mild pyrolysis. In this study, the synthesis of the nanocatalyst and pyrolisis are optimized. The research outcomes reflect a notable work towards efficiency enhancement. Initial investigations showcased the highest values before optimization for nanocatalyst synthesis, oil yield, and calorific value, which are 63.23%, 50.78%, and 10684 cal/g, respectively. However, these values increase significantly after optimization to 68.44%, 53.72%, and 10775 cal/g, respectively. Careful validation endeavors have underscored the closeness, manifesting slight errors of 2.52%, 1.86%, and 0.36% for catalyst yield, oil yield, and calorific value, respectively. This validation features the reliability of the research findings. Intriguingly, the GC-MS analysis establishes compelling parallels in composition between the derived product and conventional diesel fuel. The minimal errors and the analogous composition to diesel fuel present a promising trajectory. The results obtained from this study contribute to the development of greener and more efficient energy production technologies, paving the way for a sustainable and eco-friendly approach to utilizing energy resources.